Characterisation of deformation behaviour and damage progression of recycled aluminium alloy AA6061 - Ho, Choon Sin (2021)
Fungi have unique characteristics since they have several applications in the environment and industry due to its ability to produce the different enzyme. This study aims to isolate a new fungal strain from Pontian peatland, Johor, Malaysia to be used for dye decolourizing in the synthetic greywater as a function of laccase (LAC), manganese peroxidase (MnP) and lignin peroxidase (LiP). The bio-synthesized nanoparticles (bimetallic Zn/Cu NPs) in the secondary metabolic products generated during the enzyme production in pumpkin peels medium was evaluated for inactivating Escherichia coli and Staphylococcus aureus seeded in greywater. The fungal isolates were identified according to phenotypic characteristics and by molecular characteristic at D1/D2 region and ITS (ITS1- ITS4) sequences. The decolourization, enzyme production and inactivation process were optimised using response surface methodology (RSM). The mechanism of decolourization and inactivation process was investigated based on Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEMEDX), Fourier transforms infrared spectroscopy (FTIR), atomic force microscopy (AFM)